The color of corn: Azuaya gastronomy through literature specialization and isolation, but it is essential (Raíces: Revista de Ciencias Sociales y Políticas, 2022)
In the literary work The children of the novelist Alfonso Cuesta y Cuesta, the customs and traditions of the Austro-Ecuadorian people during the 20th century are represented. In this sense, this article has sought to expose the gastronomic contexts present in the work, those that highlight the daily life of rurality, a sector where ancient practices are currently maintained in the context of the preparation of foods such as corn, beans, potatoes. , cane, etc. In addition to the use of utensils such as grinding stones, jars, tulpa, which carry a symbolic load, and are present in these towns. In this sense, the content analysis method was applied, which served to expose the gastronomic elements present in the work, which have been contextualized and supported by documentary sources, and through a photographic record that refl ects the social reality of the rural sector. contemporary. From this perspective, the result will be that the culinary traditions in Azuay have undergone considerable changes due to the accelerated life of the modern system, choosing to prepare fast foods, losing certain traditional gastronomic practices. However, this knowledge and practices have been revalued by independent and political groups, through registration through the publication of books, articles, photographs, events, etc. carrying out programs that provide certifi cations for those who carry out these so-called ancestral practices. through ethnographic work and the same illustrations are highlighted.
Keywords: Azuay; iterature; history; gastronomy; pre-Hispanic utensils